Experimental investigation of open loop thermosyphoning in evacuated tube receiver under varying heat flux - Mat Arifin, Arief Farhan (IRC, 2020)
Thermosyphon is a mechanism involving passive heat exchange by principle of natural convection, which used to transfer fluids without any use of mechanical pump. In solar water heating system, principle of thermosyphon is applied by evacuated tube receiver (ETR). ETR is an efficient solar collector responsible of collecting and transmit the thermal energy in this process. This heating system is used heavily in the production of hot water domestically, but it also can be applied for industrial purpose, if proper innovation is designed. However, this process of optimization is expensive and time-consuming. It becomes more challenging when variables such as geographical location, solar radiation and sky condition can affect the thermosyphon performance